STRATEGI PENGEMBANGAN INDUSTRI KUSEN DI KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR - Ecil Ully Farina; Azwar Harahap; Ufira Isbah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted in sub district of bangkinang kampar district. The purpose of this research is to find out how the development of syringe industry in sub district bangkinang kampar district and to know the internal and external variables that affect the development of the framework industri in sub district bangkinang kampar district. This research uses field research techniques and questionnaires then the population is selected in this study are as many as 13 industrial units. Sample used in this research is 13 respondents and data management using SWOT method. From the result of the research shows that the framework industry in the sub district of Bangkinang Kampar district has potential to be developed. Based on matrix IFAS and EFAS known strength score and opportunity greater than the weakness and threath of the scor for strength 1,75 and probability score 1,88 while the weakness score 1,15 and the threat score is 1,04.Keywords : Industrial development, The Framework Industry, Analysis SWOT